A Comparative Study of Five Reference Materials and the Lombard Meteorite for the Determination of the Platinum‐Group Elements and Gold by LA‐ICP‐MS. Issue 1 (3rd August 2012) - Gilbert, Sarah; Danyushevsky, Leonid; Robinson, Philip; Wohlgemuth‐Ueberwasser, Cora; Pearson, Norman; Savard, Dany; Norman, Marc; Hanley, Jacob
<x xml:space="preserve">Abstract</x> A range of independently characterised reference materials (RMs) for LA‐ICP‐MS, used for the determination of the platinum‐group elements (PGE) and Au in a sulfide matrix, were analysed and compared: 8b, PGE‐A, NiS‐3, Po727‐T1, Po724‐T and the Lombard meteorite. The newly developed RM NiS‐3 was used as the RM for the calibration of all LA‐ICP‐MS analyses and the measured concentrations of the other RMs compared against their published concentrations. This data were also used to assess the consistency of concentrations calibrated against the different RMs. It was found that Po727‐T1 and 8b produced results that were comparable, within uncertainty, for all elements. Po727‐T1 also produced consistent results with NiS‐3 for all elements. All other RMs showed differences for some elements, especially Ru in Po724‐T, and Os, Ir and Au in PGE‐A. The homogeneity of the PGE and Au in each RM was assessed, by comparing the precision of multiple LA‐ICP‐MS spot analyses with the average uncertainty of the signal. Po724‐T, Po727‐T1 and the Lombard meteorite were found to be homogeneous for all elements, but 8b, PGE‐A and NiS‐3 were heterogeneous for some elements. This is the first direct comparison between a range of independently characterised PGE and Au LA‐ICP‐MS RMs.